LINGUOPOETHIC FUNCTIONS OF TERMS IN THE ARTISTIC TEXT - Turdiyeva Munisa Burxonovna (International Journal of Literature and Language Studies, 2026)
This article analyzes the role of terms in literary texts, the derived meanings of terms in poetic discourse, and their linguopoetic functions based on field sources.